Association between rumen microbiota and marbling grade in Hu sheep - Wang, Jianghui; Zhang, Yukun; Wang, Xiaojuan; Li, Fadi; Zhang, Deyin; Li, Xiaolong; Zhao, Yuan; Zhao, Liming; Xu, Dan; Cheng, Jiangbo; Li, Wenxin; Lin, Changchun; et al. (Frontiers in Microbiology, 2022)
The marbling fat regulates the flavor of mutton and measures the fat density in the loin eye and is the most important parameter of carcass grading. The objectives of this study were to explore the relationship of rumen microbiota and mutton marbling grade. One hundred and eighty-seven feedlot-finished Hu male lambs (Age: 180 day; Final BW: 46.32 ± 6.03 kg) were slaughtered, and ruminal contents and marbling grade were collected. Ruminal microbial DNA extraction and 16S rRNA gene sequencing was performed to investigate microbial composition and to predict microbial metabolic pathways. The animal cohort was then grouped based on marbling grades (LM, marbling grade ≤1; MM, 1< marbling grade ≤3; HM, 3 < marbling grade ≤5) and intramuscular fat-associated microorganisms were pinpointed using LEfSe and random forest classification model. Intramuscular fat content had significantly differences among the three groups (P <0.05), and was significantly correlated with VFAs profiling. HM sheep showed a higher abundance of one bacterial taxon (Kandleria), and two taxa were overrepresented in the MM sheep (Pseudobutyrivibrio and Monoglobus), respectively. In addition, the main intramuscular fat deposition pathway was found to involve peroxisome proliferator-activated receptor (PPAR) fatty acid synthesis. By studying the effect of the ruminal microbiome on the marbling of sheep, the present study provides insights into the production of high-quality mutton.